Sofutowea ākitekucha metorikusu ākitekucha hinshitsu o kaizensuru 10 no adobaisu = Software architecture metrics : case studies to improve the quality of your architecture / = Software architecture metrics : - Ciceri, Christian; Farley, Dave; Ford, Neal; Harmel-Law, Andrew; Keeling, Michael; Lilientha, Carola; Rosa, João; Von Zitzewitz, Alexander; Weiss, René (Orairī Japan, 2024)
Software architecture metrics are key to the maintainability and architectural quality of a software project and they can warn you about dangerous accumulations of architectural and technical debt early in the process. In this practical book, leading hands-on software architects share case studies to introduce metrics that every software architect should know. This isn't a book about theory. It's more about practice and implementation, about what has already been tried and worked. Detecting software architectural issues early is crucial for the success of your software: it helps mitigate the risk of poor performance and lowers the cost of repairing those issues. Written by practitioners for software architects and software developers eager to explore successful case studies, this guide will help you learn more about decision and measurement effectiveness. Through contributions from 10 prominent practitioners, this book shares key software architecture metrics to help you set the right KPIs and measure the results. You'll learn how to: measure how well your software architecture is meeting your goals, choose the right metrics to track (and skip the ones you don't need), improve observability, testability, and deployability, prioritize software architecture projects, and build insightful and relevant dashboards--Publisher's description.
Includes bibliographical references
Keywords: Software measurement -- Case studies; Software architecture; Mesure du logiciel; Études de cas; Architecture logicielle; Sofutōea kōgaku